Killer cell immunoglobulin-like receptor alleles influence susceptibility to occult hepatitis B infection in West African population - Momeiyi M. Bazie; Florencia W. Djigma; Mahamoudou Sanou; Pegdwendé A. Sorgho; Abdoul K. Ouattara; Dorcas Obiri-Yeboah; Nadege Kapieko; Herman K. Sombie; Prosper Bado; Edwige T. Yelemkoure; Isabelle T. Kiendrebeogo; Marius B. Nagalo; et al. (AOSIS, 2023)
Occult hepatitis B infection (OBI) is a public health problem in Burkina Faso. OBI represents a risk factor for the development of cirrhosis and hepatocellular carcinoma (HCC). OBI could be due to mutant viruses undetectable by HBsAg assays or a strong suppression of viral replication and gene expression under the pression of the host immune system. To investigate the role of killer cell immunoglobulin‑like receptor (KIR) gene polymorphisms in patients with OBI in Burkina Faso compared to healthy and chronic hepatitis B subjects. A total of 286 participants was recruited, including 42 cases of OBI, 110 cases of chronic hepatitis B and 134 HBV negative subjects. SSP‑PCR was performed to search for the presence of KIR genes. The HBV viral load was determined by qPCR. The frequencies of the activator gene KIR2DS5 (P=0.045) and the pseudogene KIR2DP1 (P0.001) in patients with OBI were higher than those in patients with chronic hepatitis B. These genes are associated with susceptibility of occult hepatitis B infection. The frequencies of the inhibitory KIR gene KIR2DL3 (P=0.01) of patients with occult hepatitis B were lower than those in chronic hepatitis B patients. This gene KIR2DL3 is associated with protection against occult hepatitis B infection. Also, the frequencies of the inhibitory KIR genes KIR2DL2 (P0.001), KIR2DL3 (P0.001) and activators KIR2DS2 (P0.001) in chronic hepatitis B patients were higher compared to the frequencies of the KIR genes in healthy subjects. These genes KIR2DL3, KIR2DL5 (A, B), KIR3DL3, KIR3DS1, KIR2DL2 and KIR2DS2 are thought to be genes associated with the susceptibility to OBI. The KIR2DS5 and KIR2DP1 genes could be associated with susceptibility to OBI. As for the KIR gene KIR2DL3 could be associated with protection against occult hepatitis B infection.